1990
DOI: 10.1084/jem.171.3.959
|View full text |Cite
|
Sign up to set email alerts
|

Soluble CD23 (Fc epsilon RII) and interleukin 1 synergistically induce early human thymocyte maturation.

Abstract: During development, lymphoid stem cells migrate into the thymic rudiment where they differentiate into functionally mature T lymphocytes (1). Among human thymocytes, CD7 + CD2 -CD3 -CD4 -CD8 -(referred hereafter as CD7') cells represent the earliest identifiable step (2-4) . In vitro, these precursors were able to acquire mature T cell antigens (3, 4), but cellular interactions and cytokines necessary for this process are poorly understood. We have previously reported that enriched populations of B lymphocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1990
1990
1994
1994

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 16 publications
1
32
0
Order By: Relevance
“…It has recently been reported that a combination of IL-1 and sCD23 induces thymocyte maturation [19]. Furthermore, in the presence of IL-1, sCD23 inhibits apoptosis of germinal centre B cells by the induction of the bcl-2 gene [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been reported that a combination of IL-1 and sCD23 induces thymocyte maturation [19]. Furthermore, in the presence of IL-1, sCD23 inhibits apoptosis of germinal centre B cells by the induction of the bcl-2 gene [20].…”
Section: Discussionmentioning
confidence: 99%
“…23]. in the progression of B lymphocytes from GO through G1 [23,24], and in the differentiation of both early human myeloid precursors and prothymocytes to thymocytes [25][26][27][28].…”
Section: Aac CC C C C C Cac C C T Cac Ca C T C T C T C Atc Atc Ccc Ccmentioning
confidence: 99%
“…FceRII/CD23can be cleaved from the surface of B lymphocytes and released in soluble frag ments (sCD23) with different molecular weights: 37, 33 and 25 kD [3], In addition to their IgE-binding function, CD23 and sCD23 exert pleiotropic activities. Soluble CD23 isoforms I his work was |>crformed jointlv in Unité Mixte INSERM UI67-CNRS f'24 and in the Service d'immunologie du Centre Hospitalier et Universitaire de Lille. are involved in the regulation of IgE production by B cells [3] and in the differentiation of early thymocytes, in syn ergy with IL-1 [4], Recombinant sCD23 can also promote the survival and differentiation of germinal center B cells, and the growth and differentiation of early myeloid pre cursor cells [5], Several studies have demonstrated that the IgE-binding region is confined to the carboxyterminal lectin homology domain [6], Flowevcr, it has recently been shown that the cytokine effects of CD23 were medi ated by a motif distinct from the IgE-binding site [7].…”
Section: Introductionmentioning
confidence: 99%